Comparison of methods for estimating leaf area in strawberry - Zeist , André Ricardo (2014)
The quantification of the plant leaf area is a tool used in the analysis of plant growth, enabling infer important parameters of plant development. Thus, the objective was to compare methods of estimating leaf area (LA), both destructive and nondestructive in strawberry. As the standard method for obtaining the leaf area, used a scanner images (Scanner), evaluating the accuracy of methods for estimating leaf area of the product of length x width of the sheet, the sum of the product of the length x width of leaflets, leaf area integrators portable and bench, squares, fresh and dry weight of leaf discs. The data of the methods evaluated in comparison to the standard method, were analyzed by simple linear correlation, determining the coefficients of determination (R2) and correlation (r), which has been tested by t test. Except for the method of integrating portable leaf area, all methods for estimating leaf area evaluated, when compared to standard method showed accuracy and can thus be used to estimate leaf area in strawberry.